New security and justice sector partnership models : implications of the Arab uprisings - McNerney, Michael J.; Moroney, Jennifer D. P., 1973-; Mandaville, Peter; Hagen, Terry; Rand eBooks (Santa Monica, CA : RAND, 2014)
The United States faces a unique set of challenges and opportunities in strengthening security and justice sector partnerships in the Middle East and North Africa. Against the backdrop of the Arab uprisings, the U.S. government has issued policy guidance relating to foreign assistance more broadly and security sector assistance in particular. RAND researchers analyzed potential new partnership models that could help implement this guidance, simultaneously strengthening security and justice sector cooperation and promoting reform across the Arab world and beyond. They devised the Enhanced Partnership Planning Model, which focuses on improving collaborative planning, rather than on using assistance as leverage to require partner nations to do what the United States wants. The model serves as a flexible framework that could support tailored, rigorous SJS planning by U.S. and partner nation stakeholders. This framework can support both policy-makers and program managers as they seek to implement new policy guidelines that integrate elements of accountability and reform while continuing to advance core U.S. interests and equities in a rapidly evolving regional context.
Introduction -- What We Know About U.S. Partnerships and Partner Characteristics -- Applying New Partnership Models -- Recommendations for Implementing the SJSP Approach.
"Prepared for the State Department Bureau of Political-Military Affairs."
"RAND National Defense Research Institute."
"This research was conducted within the International Security and Defense Policy Center of the RAND National Security Research Division (NSRD)"--Title page verso.
Includes bibliographical references (p. 67-70).
Also available on the internet via WWW in PDF format.
Keywords: Arab Spring, 2010-; United States -- Foreign relations -- Arab countries; Middle East -- Politics and government -- 21st century; Arab countries -- Foreign relations -- United States; Arab countries -- Politics and government -- 21st century; Electronic books